Aedes aegypti salivary gland extract alleviates acute itching by blocking TRPA1 channels - Cerqueira, Anderson R. A.; Rodrigues, Leandro; Coavoy-Sánchez, Silvia Abigail; Teixeira, Simone A.; Feitosa, Karla B.; Taniguchi, Erika Y.; Lopes, Lucia R.; Cassola, Antônio C.; Muscará, Marcelo N.; Sá-Nunes, Anderson; Costa, Soraia K. P. (Frontiers in Physiology, 2023)
Aedes aegypti (Ae. aegypti) saliva presents a variety of anti-inflammatory and immunomodulatory activities. Interestingly, although mosquito bites are known to cause allergic reactions in sensitized hosts, primary exposure of humans to Ae. aegypti does not evoke itching. Whether active components in the saliva of Ae. aegypti can counteract the normal itch reaction to injury produced by a histaminergic or non-histaminergic pathway in vertebrate hosts is unknown. This study was aimed at investigating the effects of the mosquito's salivary gland extract (SGE) on sensitive reactions such as itching and associated skin inflammation. Acute pruritus and skin edema were induced in mice by the intradermal injection of either compound 48/80 (C48/80), the Mas-related G protein-coupled receptor (Mrgpr) agonist chloroquine, or the transient receptor potential ankyrin 1 (TRPA1) agonist allyl isothiocyanate (AITC). By recording bouts of scratching, we showed that Ae. aegypti SGE (1 to 3 μg/site) inhibited itching, skin edema, and neutrophil influx evoked by C48/80, but it did not affect mast cell degranulation in vivo or in vitro. Additionally, SGE partially reduced chloroquine- and AITC-induced pruritus in vivo, suggesting that SGE affects pruriceptive nerve firing independently of the histaminergic pathway. Activation of TRPA1 results in a significant increase of intracellular Ca2+ in TRPA-1-transfected HEK293t lineage, which was reduced by SGE addition. We show for the first time that the SGE of the Ae. aegypti exerts anti-pruriceptive effects, being partially regulated by histamine-independent itch TRPA1 pathway, thus suggesting that SGE possess bioactive molecules with therapeutic potential for the treatment of nonhistaminergic itch.